Improvement in the inventory management process in a textile industry: a case study - Rodrigues, Emmanuel Belga; Rodrigues, Maria Eduarda Belga; Oliveira, Mário César Fialho de; Abreu, Sanderson Rocha de; Oliveira, Antônio Elízio de (Brazilian Journal of Production Engineering, 2021)
The study and design of inventory management models, based on continuous review and periodic review methodologies, allows us to evaluate the most efficient way to control stock, evaluating the quantitative way of the effects of these models on stock performance. Therefore, through the simulation environment of the proposed calculations, this study seeks to determine the ideal method for the resupply policy of a textile company. The inventory control models are compared through indicators, reducing total inventory costs, where one of them is selected as the most viable for the studied company.